Literature Review on Digital Competence, Work-Life Balance, and Technology Stress on Health Employee Performance in the Digital Era - Sunaryo, Siti Ashfiyah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The development of digital technology in the health sector has had a significant impact on the way health workers work, requiring adequate mastery of digital competencies. Previous research shows that digital skills not only have an impact on work efficiency, but are also closely related to the emergence of so-called psychological stress technostress. In addition, work-life balance (WLB) has been identified as an important factor influencing employee satisfaction and performance, especially in a very dynamic work environment such as a hospital. This study aims to examine the relationship between digital competence, work-life balance, technology stress, and health employee performance through an approach literature review. The results of the study show that digital competence makes a positive contribution to performance if supported by appropriate management and training. Meanwhile, work-life balance has been proven to increase loyalty and productivity, while techno-stress is consistently negatively correlated with performance and psychological well-being. Organizational support through flexible work policies and mental health-oriented leadership are key strategies in managing the challenges of digitalization. These findings provide practical implications for human resource management in the health sector in creating an adaptive and sustainable work environment.